Macrophage colony-stimulating factor augments Tie2-expressing monocyte differentiation, angiogenic function, and recruitment in a mouse model of breast cancer. - Mary A Forget; Jeffrey L Voorhees; Sara L Cole; Duaa Dakhlallah; Ivory L Patterson; Amy C Gross; Leni Moldovan; Xiaokui Mo; Randall Evans; Clay B Marsh; Tim D Eubank (PLoS ONE, 2014)
Reports demonstrate the role of M-CSF (CSF1) in tumor progression in mouse models as well as the prognostic value of macrophage numbers in breast cancer patients. Recently, a subset of CD14+ monocytes expressing the Tie2 receptor, once thought to be predominantly expressed on endothelial cells, has been characterized. We hypothesized that increased levels of CSF1 in breast tumors can regulate differentiation of Tie2- monocytes to a Tie2+ phenotype. We treated CD14+ human monocytes with CSF1 and found a significant increase in CD14+/Tie2+ positivity. To understand if CSF1-induced Tie2 expression on these cells improved their migratory ability, we pre-treated CD14+ monocytes with CSF1 and used Boyden chemotaxis chambers to observe enhanced response to angiopoietin-2 (ANG2), the chemotactic ligand for the Tie2 receptor. We found that CSF1 pre-treatment significantly augmented chemotaxis and that Tie2 receptor upregulation was responsible as siRNA targeting Tie2 receptor abrogated this effect. To understand any augmented angiogenic effect produced by treating these cells with CSF1, we cultured human umbilical vein endothelial cells (HUVECs) with conditioned supernatants from CSF1-pre-treated CD14+ monocytes for a tube formation assay. While supernatants from CSF1-pre-treated TEMs increased HUVEC branching, a neutralizing antibody against the CSF1R abrogated this activity, as did siRNA against the Tie2 receptor. To test our hypothesis in vivo, we treated PyMT tumor-bearing mice with CSF1 and observed an expansion in the TEM population relative to total F4/80+ cells, which resulted in increased angiogenesis. Investigation into the mechanism of Tie2 receptor upregulation on CD14+ monocytes by CSF1 revealed a synergistic contribution from the PI3 kinase and HIF pathways as the PI3 kinase inhibitor LY294002, as well as HIF-1α-deficient macrophages differentiated from the bone marrow of HIF-1αfl/fl/LysMcre mice, diminished CSF1-stimulated Tie2 receptor expression.